Opioid Sparing in Cleft Palate Surgery. (October 2018) - Carr, Logan; Gray, Megan; Morrow, Brad; Brgoch, Morgan; Mackay, Donald; Samson, Thomas
Objective: This study aimed to determine whether intraoperative acetaminophen was able to decrease opioid consumption, pain scores, and length of stay while increasing oral intake in cleft palate surgery. Design/Setting/Patients: One hundred consecutive patients with cleft palate who underwent a von Langenbeck or 2-flap palatoplasty and intravelar veloplasty at a tertiary medical center by the 2 senior authors from 2010 to 2015 were reviewed. Interventions: Three intraoperative treatment groups were analyzed: intravenous (IV) acetaminophen, per rectal (PR) acetaminophen, and no acetaminophen. All patients received long-acting local anesthesia infiltration before incision. Additionally, all patients were admitted overnight and given weight-based per oral (PO) acetaminophen and oxycodone and IV morphine as needed based on pain scores. Outcomes Measured: The study outcomes included pain scores, opioid requirement, length of stay, and oral intake. Results: The treatment groups were comprised of 40 patients who received IV acetaminophen, 22 PR acetaminophen, and 35 none. Concerning demographic data, there was no statistical difference between treatment groups. There was no statistically significant difference for opioid intake, although both IV and PR acetaminophen groups had decreased pain scores ( P = .029). There was no difference in oral intake ( P = .13) or length of stay ( P = .31) between treatment groups. Conclusion: In this study, intraoperative administration of acetaminophen was associated with decreased pain scores, but no opioid-sparing effect. As other studies have shown an opioid-sparing effect with postoperative acetaminophen, we recommend withholding the intraoperative dose and beginning therapy in the immediate postoperative period.